Migração de Prochilodus lineatus (Valenciennes, 1836) através de escada para peixes em usina hidrelétrica: gatilhos migratórios e conectividade bidirecional - Celestino, Leandro Fernandes (2018)
The reproductive migration is an adaptative phenomenon which is essential for species perpetuation. The migratory fish species have been evolved to identify the environmental cues to timing their migration with optimal environmental conditions, thus maximizing the reproduction and offspring survival. However, the conservation of potamodromous species have been threatened due to the loss of bidirectional connectivity and alterations of hydrological regimes imposed by dams. One management strategy to reestablish the connectivity is to build fishways, although they have been described as ascending one-ways in Neotropical rivers. Therefore, this study evaluated the migratory behavior of Prochilodus lineatus (Valenciennes, 1836) over 4 years in the fish ladder of HPP Engenheiro Sergio Motta (also known as Porto Primavera). We monitored the fish ladder continuously with the RFID system (Radio Frequency Identification). Overall, 1,419 specimens of P. lineatus were tagged with PIT-tag (Passive Integrated Transponder) and released in downstream and upstream of Porto Primavera dam. The aims were understanding the reproductive migratory behavior of P. lineatus in response to environmental factors and identify whether fish are able to use the fish ladder in both directions, ascending and descending. The reproductive migration of P. lineatus was influenced for synchronizing triggers. Besides that, the results indicate that only part of P. lineatus population use the fish ladder. However, some individuals are able to use the fish ladder in both directions over their life cycle.